2023
DOI: 10.1159/000528316
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Resistance in Schizophrenia Is Associated with Attention Deficit/Hyperactivity Disorder and Gut Microbiota: A Genetic Correlation and Mendelian Randomization Study

Abstract: <b><i>Introduction:</i></b> Observational studies highlight associations of common diseases with individual schizophrenia symptoms. However, it is unclear whether these diseases are associated with individual treatment-resistant schizophrenia (TRS). We aimed to explore the genetic associations between common immune diseases, metabolic diseases, psychiatric disorders, gut microbiota and TRS. <b><i>Methods:</i></b> Genome-wide association study (GWAS) summary data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Thanks to large-scale GWAS of gut microbiotas in different diseases, MR has been widely used to study disease pathogenesis. Indeed, several studies using MR have now established that the gut microbiota is strongly associated with several neurological diseases including Alzheimer’s disease ( Zeng et al, 2023 ), major depressive disorder ( Chen M. et al, 2022 ), schizophrenia ( Cheng et al, 2023 ), and insomnia ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to large-scale GWAS of gut microbiotas in different diseases, MR has been widely used to study disease pathogenesis. Indeed, several studies using MR have now established that the gut microbiota is strongly associated with several neurological diseases including Alzheimer’s disease ( Zeng et al, 2023 ), major depressive disorder ( Chen M. et al, 2022 ), schizophrenia ( Cheng et al, 2023 ), and insomnia ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most observational studies have shown that patients with specific dermatitis often have intestinal flora disturbance, but this may only be a clinical symptom of specific dermatitis and cannot prove a causal relationship (observational studies may have differences in intestinal flora due to grouping requirements, sex ratio, ethnicity, etc.). Therefore, MR is adopted to eliminate the interference of confounding factors on the one hand and avoid the influence of reverse causality on the other hand, so as to make the study more rigorous and credible ( 22 ).…”
Section: Introductionmentioning
confidence: 99%